1978
DOI: 10.1111/j.1365-3083.1978.tb00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered Proportion of Tμ and Tγ‐Cell Subpopulations in Patients with Hodgkin's Disease

Abstract: The ability of peripheral blood lymphocytes from patients with Hodgkin's disease (HD) to form rosettes with ox red blood cells (ORBC) sensitized by anti-ORBC purified rabbit IgM and IgG was investigated. The mean percentage of cells capable of forming rosettes with ORBC coated with IgM (EAIgM-RFC) in the peripheral blood of either untreated or X-ray-treated patients with HD was significantly lower than that of normal individuals. In the same groups of patients with HD the mean percentage of T lymphocytes equip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
2

Year Published

1979
1979
1985
1985

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 11 publications
(10 reference statements)
3
7
2
Order By: Relevance
“…Our results would appear to be at variance with an earlier study (Romagnani et al, 1978) which showed an imbalance of subsets of peripheral-blood T-cells subsets in HD patients. Such cells identified as Er+ cells expressing receptors for either IgM(TIi) or IgG (Ty), have been described by others (Moretta et al, 1977) as subserving "helper"/"inducer" and "suppressor"/" cytotoxic" functions respectively.…”
Section: T Lymphocytescontrasting
confidence: 56%
“…Our results would appear to be at variance with an earlier study (Romagnani et al, 1978) which showed an imbalance of subsets of peripheral-blood T-cells subsets in HD patients. Such cells identified as Er+ cells expressing receptors for either IgM(TIi) or IgG (Ty), have been described by others (Moretta et al, 1977) as subserving "helper"/"inducer" and "suppressor"/" cytotoxic" functions respectively.…”
Section: T Lymphocytescontrasting
confidence: 56%
“…2). The effect of B cells on the response to PPD observed in this study was, however, much less striking than that reported by Blomgren [6j and Romagnani et a1 [7], as we found them to be only minimally involved in the response to PPD. On the other hand, our results disagree with those reported previously by others…”
Section: Discussioncontrasting
confidence: 78%
“…In addi tion, it was shown that this increase in EA-RFC was present in the T-cell population. Imbalances in the T-cell subsets in Hodg kin's disease have also been reported in other studies [25][26][27][28]. Beck et al [29] demonstrated imbalances in the T-cell subsets in patients with non-Hodgkin lym phoma, a finding that could have been present in our NHL patients with high percentages of EA-RFC.…”
Section: Discussionsupporting
confidence: 53%